Influence of the level of physical activity on the body mass index and changes in eating habits in university students in the northern region of brazil during the COVID-19 pandemic (Research, Society and Development, 2023)
Objective: To verify the influence of physical activity level (PAL) on body mass index (BMI) and eating habits in college students during the COVID-19 Pandemic. Methods: This was a cross-sectional study, using an online questionnaire with college students from northern Brazil of both genders (40.3% men; 59.4% women) with a mean age of 26.2 ± 8.6 years, BMI (kg/m²) 25.1 ± 5.9, and was obtained by the ratio between body mass (kg) divided by height (m) squared, self-reported. The evaluation of eating habits was performed using an online questionnaire, based on the scale of dietary assessment according to the Brazilian Population Food Guide. Results: Habits data show that 28.3% never take any food with them for consumption throughout the day. No significant associations were found between physical activity level (active 51.2% and inactive 46.7%) and BMI (normal), P=0.444. Conclusion: Additionally, only one variable had significance between physical activity level and eating habits (P = 0.033), for the other variables there was no significant association (P>0.05).